Digital Technology Adoption and Jobs : A Model of Firm Heterogeneity - Brambilla, Irene (World Bank, Washington, DC, 2018)
This paper develops a theoretical framework that expands the task-based models of technical progress and labor markets to allow for firm heterogeneity and wages that vary across firms. The model is compatible with the empirical observation that more productive firms are larger, are more skill intensive, and pay higher wages across skill categories. The model predicts that the decision to invest in information and communications technology depends on firm size and labor market characteristics. As a result of investment in information and communications technology firms grow, become more intensive in complex tasks, become more skilled intensive, and employ more skilled workers as long as skilled labor is complementary to information and communications technology. Employment of unskilled workers increases as well, provided that firm output growth is sufficiently high to overcome the negative substitution effect. Workers who remain employed are better off because their wage increases with information and communications technology. To the extent that skilled workers have more bargaining power than unskilled workers, or that their wage scheme is more tied to firm performance, wage inequality at the firm level increases with information and communications technology.